BIOTRANSFORMASI 2E-6E-FARNESOL OLEH JAMUR ENDOFIT BOTRYOSPHAERIA SP. CA2C-3 YANG DIISOLASI DARI TEMU HITAM (CURCUMA AERUGINOSA ROXB.) - Agusta, Andria (Perhimpunan Biologi Indonesia, 2013)
The objective of study was to investigate the microbial transformation reaction of 2E-6E-farnesol by the endophyticfungi isolated from temu hitam (Curcuma aeruginosa ROXB. The transformation was carried out in PDB with (2E-6E-farnesol), incubated at room temperature (25-32o C) under shaking condition at 120 rpm for two days produceda major biotransformed product. Structure elucidation based on 1D- and 13C-NMR analysis showed that the biotransformedproduct was 10,11-dihydroxi-2E-6E-farnesol. It It was verified that biotransformation reaction of 2E-6E-farnesol into 10,11-dihydroxi-2E-6E-farnesol through an intermediate 10,11-epoxi-2E-6E-farnesol.Keywords: Temu hitam; Curcuma aeruginosa; endophytic fungi; biotransformation; 2E,6E-farnesol; 10,11-dihydroxi-2E,6E-farnesol; 10,11-epoxi-2E-6E-farnesol.